Упровадження мультимедійних технологій у навчальний процес: проблеми і перспективи - Васецька, Лариса Іванівна; Соловйова, Ольга Володимирівна; Васецкая, Л. И.; Соловьева, О. В.; Vasetska, L.; Solovyova, O. (Харківський національний університет імені В. Н. Каразіна, 2019)
У статті розглядається питання розвитку вищої освіти, формування нової моделі навчального процесу у нефілологічних закладах вищої освіти. Зазначається, що нова модель навчального процесу орієнтована на активну модернізацію освіти, підвищення якості освіти, більш ефективне використання навчального часу і забезпечення потреб кожного студента відповідно до його індивідуальних можливостей завдяки використанню у навчальному процесі інформаційних технологій. В статье рассматривается вопрос развития высшего образования, формирования новой модели учебного процесса в нефилологических высших учебных заведениях. Отмечается, что новая модель учебного процесса ориентирована на активную модернизацию образования, повышение качества образования, более эффективное использование учебного времени и обеспечение потребностей каждого студента в соответствии с его индивидуальными возможностями благодаря использованию в учебном процессе информационных технологий. The article deals with the issue of the development of higher education, the formation of a new model of educational process in non-philological higher schools. It is noted that the new model of educational process is focused on active modernization of education, improving the quality of education, more accordance with his individual abilities through the use of information technologies in the educational process. Today the task of most linguistic departments and language training centers for foreign students of higher education in Ukraine is to search and develop innovative teaching technologies and advanced forms and methods of teaching students, the introduction of the results of advanced world scientific schools into the practice of teaching non-native language. The urgency of the problem lies in the fact that in today’s demanding and rapidly changing environment, the level of education depends to a large extent on the effectiveness of the introduction of modern technologies into learning, based on new methodological principles, modern didactic principles and psychological and pedagogical theories. Of course, computer does not replace the teacher, but is only a means of carrying out a pedagogical activity, his assistant. However, it should be noted that when using multimedia, the role of a teacher changes significantly: he begins to use teaching time more effectively, focusing on individual assistance to students, on the discussion of information, on the development of their creative approach. Despite the large number of new educational technologies, one should not consider any of them as self-sufficient. Perhaps the one that integrates a complex of achievements of several methods, that is transformed depending on the methodological preferences, the content of the discipline, the equipping of the educational process, the level of students, the level of professional training, will be the most effective.
Внедрение мультимедийных технологий в учебный процесс: проблемы и перспективы
Implementation of multimedia technologies in the educational process: problems and prospects
Keywords: інноваційні технології; когнітивна структура; мультимедіа; нова парадигма вищої освіти; педагогічні технології; инновационные технологии; когнитивная структура; мультимедиа; новая парадигма высшего образования; педагогические технологии; cognitive structure; innovative technologies; multimedia; new paradigm of higher education; pedagogical technologies